2022
DOI: 10.3390/jcm11195600
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Occupation on the Prevalence of Spinal Pain among Physiotherapists and Nurses

Abstract: (1) Background: Neck pain (NP) and low back pain (LBP) are common musculoskeletal disorders, one of the major causes of disability globally. The aim of the study was to determine the influence of medical occupation (physiotherapist and nurse) on the prevalence of spinal pain, functional status and degree of disability. (2) Methods: a total of 544 people (462 females (84.9%) and 82 males (15.1%)), licensed to practice as a physiotherapist (n1 = 240 (44.1%)) or nurse (n2 = 304 (55.9%)) in Poland completed a spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
1
2
1
Order By: Relevance
“…However, this was not the case for the prevalence of LBP in the previous 12 months (57.1% in France versus 22.0% to 73.1% for studies performed in other countries) [13,14]. The prevalence in the previous 12 months reported in the present study was lower than that described for other healthcare workers: 80% and 88.5% among nurses in studies by Jradi et al (2020) [38] and Bryndal et al (2022), respectively [39], 74% among operating room personnel [40], and 65% among obstetric care providers [41].…”
Section: Discussioncontrasting
confidence: 86%
“…However, this was not the case for the prevalence of LBP in the previous 12 months (57.1% in France versus 22.0% to 73.1% for studies performed in other countries) [13,14]. The prevalence in the previous 12 months reported in the present study was lower than that described for other healthcare workers: 80% and 88.5% among nurses in studies by Jradi et al (2020) [38] and Bryndal et al (2022), respectively [39], 74% among operating room personnel [40], and 65% among obstetric care providers [41].…”
Section: Discussioncontrasting
confidence: 86%
“…In terms of the effects of occupational stress on participants’ physical health, pain (waist, back, body, and headaches) was experienced, and this concurs with Bryndal et al (2022) , who demonstrated that excessive strain of the spine associated with occupational activities has a strong impact on the intensity and frequency of spinal pain episodes and that physiotherapists and nurses mainly suffer from low back pain. Adhikari and Dhakal (2015) observed 50% absenteeism among nurses by sick leave due to low back pain, many of them and many more could not perform their job properly because of low back pain.…”
Section: Discussionsupporting
confidence: 79%
“…This could potentially result in lower back and neck discomfort. Following a study conducted by Bryndal et al [20] in Poland, dental staff may experience neck pain due to various occupational factors. These factors include a fast-paced work environment, repetitive movement patterns, inadequate recovery time, weightlifting, poor posture, mechanical pressure, flexion, torsion, vibrations, and exposure to low temperatures.…”
Section: Resultsmentioning
confidence: 99%